2020
DOI: 10.4314/ahs.v20i2.44
|View full text |Cite
|
Sign up to set email alerts
|

Weight reduction improves immune system and inflammatory cytokines in obese asthmatic patients

Abstract: Background: Activation of immunological and systemic inflammation markers are common in obesity and asthma. Objective: The target of this study was to assess impact of weight reduction on immunological and systemic inflammation markers in obese asthma patients. Material and methods: Eighty asthmatic patients of both sex; their age and body mass index (BMI) mean were 38.72 ± 7.14 year and 32.65 ± 3.18 Kg/m2 respectively. Exclusion criteria included smokers, infections, vaccinations, cancer, surgery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(37 reference statements)
0
11
0
1
Order By: Relevance
“…A total of 12 studies (62%) 10,[27][28][29][30][31][32][33][34][35][36][37] showed that AT induced some change in the immune system inflammatory response, while 9 studies (38%) [38][39][40][41][42][43][44][45] did not show any change in the immune system. In complement, other general benefits were observed such as improvements in the aerobic fitness (10 studies), health-related quality of life (7 studies), clinical control (2 studies), reduction of symptoms of asthma (6 studies), and decrease of airways hyperresponsiveness (2 studies) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 studies (62%) 10,[27][28][29][30][31][32][33][34][35][36][37] showed that AT induced some change in the immune system inflammatory response, while 9 studies (38%) [38][39][40][41][42][43][44][45] did not show any change in the immune system. In complement, other general benefits were observed such as improvements in the aerobic fitness (10 studies), health-related quality of life (7 studies), clinical control (2 studies), reduction of symptoms of asthma (6 studies), and decrease of airways hyperresponsiveness (2 studies) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that AT induces a modulation of the immune system 10,[27][28][29][30][31][32][33][34][35][36][37] . In this sense, the present study speculates on two categories of asthmatics, i) those who practice regular exercise or are trained; ii) and those who are untrained or sedentary.…”
Section: Possible Protective Pathways Against Covid-19 Presented By S...mentioning
confidence: 99%
“…A total of nine studies were identified, including six RCTs [97][98][99][100][101][102] and three single group pre-post studies [103][104][105] (Table 1). The number of participants across the studies ranged from 27 to 330 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the last few decades, the prevalence of obesity and allergic diseases is increasing worldwide in adults and children (1)(2)(3)(4). Several experimental and clinical studies suggested relationships between obesity, allergies and asthma, however the underlying mechanisms linking these diseases are still not well understood (5)(6)(7)(8). Vitamin D is an important regulator of the immune system, and low vitamin D status has been associated with several immune-mediated diseases such as multiple sclerosis, inflammatory bowel disease, and allergic asthma (9-13).…”
Section: Introductionmentioning
confidence: 99%